Analisis Kuantitatif Kadar Tembaga (Cu) dalam Sampel Air Menggunakan Spektrofotometri UV-Vis - Ekawati, Linda; Maliki , Syariful (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The presence of copper metal (Cu²⁺) in water needs to be analyzed because its concentration can affect the quality and safety of water, especially for consumption. This study aims to determine the levels of Cu²⁺ in various water samples using the UV-Vis spectrophotometry method with ammonia (NH₃) complexing. Copper ions form a blue complex [Cu(NH₃)₄]²⁺ which is analyzed at a maximum wavelength of 615 nm. The calibration curve was obtained from a standard solution with the linear equation y = 0.0016x + 0.0003, which was used to calculate the concentration of Cu in water samples. The results of the analysis showed that the concentration of Cu in gallon water, bottled water, PDAM water, and well water I was still below the maximum limit of 2.0 mg/L set by the Indonesian Minister of Health Regulation No. 2 of 2023, while well water II had a Cu content of 6.688 ppm, exceeding the safe limit. Sources of Cu ions in water can come from weathering of rocks containing copper minerals or anthropogenic activities such as industrial waste. Excessive Cu content in the body has the potential to cause health problems. Therefore, water with high Cu levels requires further treatment, such as adsorption, ion exchange, or phytoremediation, before being used for consumption purposes.